Clozapine Combination and Augmentation Strategies in Patients With Schizophrenia —Recommendations From an International Expert Survey Among the Treatment Response and Resistance in Psychosis (TRRIP) Working Group. (18th May 2020) - Wagner, Elias; Kane, John M; Correll, Christoph U; Howes, Oliver; Siskind, Dan; Honer, William G; Lee, Jimmy; Falkai, Peter; Schneider-Axmann, Thomas; Hasan, Alkomiet; ,
Abstract: Background: Evidence for the management of inadequate clinical response to clozapine in treatment-resistant schizophrenia is sparse. Accordingly, an international initiative was undertaken with the aim of developing consensus recommendations for treatment strategies for clozapine-refractory patients with schizophrenia. Methods: We conducted an online survey among members of the Treatment Response and Resistance in Psychosis (TRRIP) working group. An agreement threshold of ≥75% (responses "agree" + "strongly agree") was set to define a first-round consensus. Questions achieving agreement or disagreement proportions of >50% in the first round, were re-presented to develop second-round final consensus recommendations. Results: Forty-four (first round) and 49 (second round) of 63 TRRIP members participated. Expert recommendations at ≥75% agreement included raising clozapine plasma levels to ≥350 ng/ml for refractory positive, negative, and mixed symptoms. Where plasma level-guided dose escalation was ineffective for persistent positive symptoms, waiting for a delayed response was recommended. For clozapine-refractory positive symptoms, combination with a second antipsychotic (amisulpride and oral aripiprazole) and augmentation with ECT achieved consensus. For negative symptoms, waiting for a delayed response was recommended, and as an intervention for clozapine-refractory negative symptoms, clozapine augmentation with an antidepressant reached consensus. For clozapine-refractory suicidality, augmentation with antidepressants or mood-stabilizers, and ECT met consensus criteria. For clozapine-refractory aggression, augmentation with a mood-stabilizer or antipsychotic medication achieved consensus. Generally, cognitive-behavioral therapy and psychosocial interventions reached consensus. Conclusions: Given the limited evidence from randomized trials of treatment strategies for clozapine-resistant schizophrenia (CRS), this consensus-based series of recommendations provides a framework for decision making to manage this challenging clinical situation.